Positive serum ethanol concentration on admission to hospital as the factor predictive of treatment outcome in acute methanol poisoning - Zakharov, Sergey; Nurieva, Olga; Kotikova, Katerina; Belacek, Jaromir; Navratil, Tomas; Pelclova, Daniela (Monatshefte fur chemie, 2017)
ABSTRACT: Mass methanol poisonings present a serious problem for health systems worldwide, with poor outcome associated with delayed treatment. Positive pre-hospital serum ethanol concentration may have predictive value as the prognostic factor of the treatment outcome. We studied the effect of positive serum ethanol level on admission to hospital on survival in patients treated during the Czech methanol outbreak during 2012-2014. Cross-sectional cohort study was performed in 100 hospitalized patients with confirmed methanol poisoning. Pre-hospital ethanol was administered in 42 patients (by paramedic/medical staff to 30 patients and self-administered by 12 patients before admission); 58 patients did not receive pre-hospital ethanol. Forty-two patients had detectable serum ethanol concentration on admission to hospital [median 18.3 (IQR 6.6-32.2) mmol dm-3]. Pre-hospital ethanol administration by paramedic/medical staff had a significant effect on survival without visual and CNS sequelae when adjusted for arterial blood pH on admission (OR 8.73; 95 % CI 3.57-21.34; p < 0.001). No patients receiving pre-hospital ethanol died compared with 21 not receiving (p < 0.001). Positive serum ethanol concentration on admission to hospital was a predictor for survival without health sequelae when adjusted for arterial blood pH (OR 8.10; 95 % CI 2.85-23.02; p < 0.001). The probability of visual and CNS sequelae in survivors reduced with increasing serum ethanol concentration on admission.
Keywords: Sequelae of poisoning; Pre-hospital ethanol administration; Methanol poisoning; Factors predictive of survival; Prognosis; First aid in methanol poisoning